How to Govern a University Effectively - Benner, Mats (Edward Elgar Publishing, 2026)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. How do you govern a university to make it effective in the real world? This informative book explores the increasingly complex challenges in governing and managing contemporary universities. Mats Benner demonstrates how institutions can best respond to changing social, economic and political dynamics to ensure their efficient operation and continued growth.